Development and Validation of a Pediatric Sports Activity Rating Scale: The Hospital for Special Surgery Pediatric Functional Activity Brief Scale (HSS Pedi-FABS). (October 2013) - Fabricant, Peter D.; Robles, Alex; Downey-Zayas, Timothy; Do, Huong T.; Marx, Robert G.; Widmann, Roger F.; Green, Daniel W.
Background: Having simple and reliable validated outcome measures is vital to conducting high-quality outcomes research in the field of orthopaedic surgery. Activity level is a key prognostic variable for patients with sports injuries. There is a paucity of such activity scales for children and adolescents who are otherwise healthy and athletically active. In addition to frequency and intensity of athletic activity, level of play and coach/trainer supervision are important variables unique to children and adolescents that are not captured in available adult scoring systems. Purpose: To create and validate a concise and comprehensive activity rating scale for athletically active children and adolescents 10 to 18 years of age. Study Design: Cohort study (diagnosis); Level of evidence, 2. Methods: Item generation was performed with a panel of orthopaedic surgeons and adolescent athletes. Item reduction, pilot testing and scale refinement resulted in a final 8-item instrument, the Hospital for Special Surgery Pediatric Functional Activity Brief Scale (HSS Pedi-FABS). Existing methods were used to determine reliability and validation. The Flesch-Kincaid score was calculated at a 6.6th-grade reading level (approximately 13 years old); therefore, although all subjects provided their own answers, parents were allowed to assist children younger than 13 years with reading the questionnaire. Results: Scale reliability was excellent (test-retest reliability, intraclass correlation coefficient = 0.91; internal consistency, Cronbach alpha = .914), and there were no floor or ceiling effects. There was also robust construct validity: Convergent validity testing revealed positive correlations between the HSS Pedi-FABS and level of competition in athletic activity, number of reported hours of athletic activity per week, and existing comparable adult and pediatric scales. Discriminant validity was shown with age, body mass index, and type of sport as measured by the Daniel scale. Conclusion: The 8-item HSS Pedi-FABS can be used to reliably and accurately evaluate activity level as a prognostic variable for clinical research studies. It is a simple, reliable, and valid metric to assess activity in children and adolescents 10 to 18 years of age. This instrument will lead to better evaluation of posttreatment outcomes and patient-reported activity for child and adolescent athletes.